A Systematic Review of Telehealth and Sport-Related Concussion: Baseline Testing, Diagnosis, and Management. Issue 1 (February 2021) - Toresdahl, Brett G.; Young, Warren K.; Quijano, Brianna; Scott, Daphne A.
Background: The use of telehealth has increased as a result of the COVID-19 pandemic. As sports at all levels resume, sports medicine physicians may be interested in how telehealth can be used for concussion care. Questions/Purpose : We sought to assess how telehealth has been used in the baseline testing, diagnosis, and/or management of concussion. Secondarily, we sought to assess the strengths and weaknesses of telehealth for concussion care and identify aspects of concussion care for which telehealth has not yet been studied. Methods : A systematic review was performed in September 2020 of PubMed and Embase using the following terms: concuss*, "mild traumatic brain, " "head injur*, " telehealth, telemedicine, telecare, "mobile health, " m-health, virtual. Studies included were original research articles investigating the use of telehealth in the care of concussion (including baseline testing, diagnosis, and management), published in English, and had full text available. Results : A total of 356 articles were screened, of which 5 were determined to meet inclusion criteria. These articles described the use of telehealth for managing concussion in military and rural settings. No articles involved the use of telehealth for baseline concussion testing of athletes or for sideline evaluation. Conclusion : Despite the limited original research on the use of telehealth for concussion care, the articles identified provide a foundation for exploring the potential value of telehealth in the office practice and sports team setting. Telehealth may expand the ability of a sports medicine physician to provide timely and effective concussion care to athletes during the COVID-19 pandemic and beyond. More rigorous research is needed.